ISLAMIC CINVENTION CENTER NAHDHATUL KAHAIRAAT DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR - Talibe, Mohamad Anwar; Tamrin, Moh. Muhrim; antu, Evi Sunarti (Program Studi Teknik Arsitektur, Fakultas Teknik - Universitas Ichsan Gorontalo, 2022)
Besides Al-Khairaat Foundation playing a role in the field of education, it also takes a part in the field of da'wah and community development. Da'wah is not merely the appearance of a preacher by merely expressing religious values in society. It also contains a broad understanding covering all aspects of life, especially in the Sangtombolang subdistrict. The Islamic Convention Center of Nahdhatul Khairaat provides an identity for Cempaka village, Sangtombolang subdistrict. It is the reason for the planning of the building